Enhanced Mineral Preservation Rather Than Microbial Residue Production Dictates the Accrual of Mineral‐Associated Organic Carbon Along a Weathering Gradient - Erxiong Zhu; Zongguang Liu; Lixiao Ma; Jianing Luo; Enze Kang; Ya Wang; Yunpeng Zhao; Juan Jia; Xiaojuan Feng (Geophysical Research Letters)
Abstract Mineral preservation and microbial residue production are vital for the accumulation of mineral‐associated organic carbon (MAOC) in soils. However, their relative importance and interactive effects remain unclear. Here MAOC content and composition are analyzed in tandem with soil mineral and microbial attributes along a weathering gradient on a volcanic soil sequence. We find that MAOC content increases with increasing mineral weathering states, accompanied by increasing microbial contribution to MAOC. Mineral attributes rather than microbial physiological traits are strongly related to MAOC contents, suggesting that weathering‐enhanced mineral preservation capacity overrides microbial residue production in governing MAOC accumulation by increasing reactive minerals. Furthermore, mineral attributes have a strong interactive effect with microbial traits on MAOC accumulation and composition, likely related to increasing fungal abundance in the microbial community with increasing weathering. These findings highlight that mineral weathering may effectively boost persistent SOC in synergy with microbial conversion in the long term.